Monitoring of CoS2 reactions using high-temperature XRD coupled with gas chromatography (GC). Issue 2 (18th April 2016) - Rodriguez, Mark A.; Coker, Eric N.; Griego, James J. M.; Mowry, Curtis D.; Pimentel, Adam S.; Anderson, Travis M.
Abstract : High-temperature X-ray diffraction with concurrent gas chromatography (GC) was used to study cobalt disulfide cathode pellets disassembled from thermal batteries. When CoS2 cathode materials were analyzed in an air environment, oxidation of the K(Br, Cl) salt phase in the cathode led to the formation of K2 SO4 that subsequently reacted with the pyrite-type CoS2 phase leading to cathode decomposition between 260 and 450 °C. Independent thermal analysis experiments, i.e. simultaneous thermogravimetric analysis/differential scanning calorimetry/mass spectrometry (MS), augmented the diffraction results and support the overall picture of CoS2 decomposition. Both gas analysis measurements (i.e. GC and MS) from the independent experiments confirmed the formation of SO2 off-gas species during breakdown of the CoS2 . In contrast, characterization of the same cathode material under inert conditions showed the presence of CoS2 throughout the entire temperature range of analysis.